Pemberdayaan Penyandang Disabilitas oleh Sheltered Workshop Peduli “Sambung Roso” di Desa Simbatan Kecamatan Nguntoronadi Kabupaten Magetan - Astutik, Sindi; Nawangsari, Ertien Rining (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
People with disabilities are people who have privileges that make them different from normal people. Even though they are different, persons with disabilities have the right to receive empowerment like other citizens. Magetan Regency is one of the areas that has shelter for persons with disabilities, namely the Sheltered Workshop Peduli (SWP) “Sambung Roso”. Empowerment is carried out by providing training to make splashed batik to persons with disabilities. The purpose of this study was to find out how the empowerment of persons with disabilities by SWP